Fabrication of p-i-n solar cells utilizing ZnInON by RF magnetron sputtering. Issue 1741 (16th March 2015) - Matsushima, Koichi; Shimizu, Ryota; Ide, Tomoaki; Yamashita, Daisuke; Seo, Hyunwoong; Koga, Kazunori; Shiratani, Masaharu; Itagaki, Naho
ABSTRACT: We succeeded in photovoltaic power generation of p-i-n solar cells utilizing epitaxial ZnInON film with a wide band gap of 3.1 eV as the intrinsic layer, suitable for a top cell of tandem solar cells. The solar cell shows a high open circuit voltage (Voc ) of 1.68 V under solar simulator light irradiation of 3.2 mW/cm 2 . The solar cell performance becomes worse under 100 mW/cm 2, which is mainly attributed to the leakage current caused by crystal defects and grain boundaries. X-ray diffraction analysis reveals that the ZnInON film has rather large tilt and twist angles and a high dislocation density of 7.62×10 10 cm -2 . Such low crystallinity is a bottleneck for high performance of the solar cells. Our results demonstrate a potential of epitaxial ZnInON films as an intrinsic layer of wide band gap p-i-n solar cells with a high Voc .